IMMU-14. IMMUNE CHECKPOINT INHIBITOR THERAPY FOR TREATMENT OF SYNCHRONOUS CANCERS IN PAEDIATRIC PATIENTS WITH CONSTITUTIONAL MISMATCH REPAIR DEFICIENCY. (4th December 2020) - Henderson, Jacob; Morgenstern, Daniel; Edwards, Melissa; Sudhaman, Sumedha; Kram, David; Osborn, Michael; Cho, Yoon-Jae; Tabori, Uri
Abstract: Constitutional mismatch repair deficiency (CMMRD) is an autosomal recessive condition in which affected patients carry biallelic germline mutations in the MMR genes. This highly penetrant syndrome results in nearly universal development of malignant neoplasms at a young age, most commonly pediatric brain tumors. Importantly, in addition to brain tumors, patients frequently develop multiple metachronous or even synchronous tumors making it impossible to treat these cancers with current chemotherapeutic approaches due to the complexity of different chemoradiation regimens required, resulting in excess toxicity and lack of efficacy. We first, assessed the metachronous (defined here as serial tumors diagnosed >1 year apart or after completion of definitive treatment for the initial tumor) or synchronous cancers (defined here as tumors diagnosed within a year of each other or during the definitive treatment for the initial tumor) in all patients within the consortium. Strikingly, 47% developed synchronous and/or metachronous cancers leading to patient demise. Molecular analysis revealed that all synchronous tumors (n=26) harbored a hypermutational burden accompanied by high genomic microsatellite instability and the relevant signatures. We therefore treated two patients with glioblastomas who had synchronous solid tumors with checkpoint inhibitors. In both patients, objective tumor response was associated with clinical benefit and prolonged survival. Biomarker analysis revealed increased tumor mutational burden, microsatellite instability and immune cell infiltration. These cases highlight the role of universal, mechanism based and tumor-agnostic approach to treat patients with brain tumors with additional synchronous cancers in the setting of cancer predisposition.